Fast GMTI Algorithm For Traffic Monitoring Based On A Priori Knowledge - Baumgartner, Stefan V.; Krieger, Gerhard (IEEE Transactions on Geoscience and Remote Sensing, 2012)
In this paper, a fast a priori knowledge-based ground moving target indication and parameter estimation algorithm applicable to single-as well as to multichannel synthetic aperture airborne radar data is presented. The algorithm operates directly on range-compressed data. Only the intersection points of the moving vehicle signals with the a priori known road axes, which are mapped into the range-compressed data array, are evaluated. For moving vehicle detection and parameter estimation, basically only a single 1-D fast Fourier transformation has to be performed for each considered road point. Hence, the required computational power is low, and the algorithm is well suited for real-time traffic monitoring applications. The proposed algorithm enables the estimation of the position and velocity vectors of detected moving vehicles independent of the number of channels. A single-channel synthetic aperture radar system may be sufficient in case of fast moving vehicles. The paper includes a detailed performance assessment together with experimental results that demonstrate the applicability in a real-world scenario. © 2012 IEEE.
DLR Import::2019-04-02
Keywords: Pulse Doppler radar; radar signal processing; road vehicle detection; synthetic aperture radar (SAR)